Produktivitas Panen Propolis Mentah Lebah Trigona itama Cockerell (Hymenoptera: Apidae) Menggunakan Propolis Trap dan Manipulasi Lingkungan di Riau - Avry Pribadi (Fakultas Biologi | Universitas Jenderal Soedirman, 2020)
Trigona itama is one species of stingless honeybees that produce more propolis than genus Apis and commonly practiced in Riau. Nowadays, the value of raw propolis is very expensive. However, techniques and methods to obtain propolis from T. itama`s were usually conducted by destroying nests that resulted in declining development and caused absconding. The objectives of this study were (1) to know the effectivity of propolis trap on T. itama box hive and (2) to examine the best manipulation technique of vegetation rotations of nectareous, pollen, and resin plants to stimulate the formation of raw propolis. Factorial Randomized Completly Design with two factors (the type of box and nectareous plant rotation schedule) was used as experimental design. Results showed that there was no significant interaction between the rotation techniques of nectareous plants and the type of propolis traps on raw propolis production. Also, by using strimin wire either on the side or on the top of box hive as propolis trap had significant value (37.20 ± 1.38 gram and 34.97±0.80 gram respectively) compared to plastic mica either on the side or top side (14.77 ± 0.16 and 12.80 ± 0.64 gram respectively). Yet, there is no significant effect of nectareous plants` (Shorea sp.) duration on the production of raw propolis.